SOCIAL WORK SERVICES TO VICTIMS OF XENOPHOBIA - van der Westhuizen, Marichen; Kleintjes, Lindy (Social Work/Maatskaplike Werk, 2015)
<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The ongoing reports of xenophobic incidents in South Africa require, amongst other things, that the role of the social work profession be explored to ensure that effective services are developed and implemented. This qualitative study explored and described social workers’ perceptions regarding the profession’s role in service delivery to victims of xenophobia in an attempt to make recommendations in this regard. The findings highlight that there is a need for clear guidelines, that programmes and resources should be available, that social workers must receive education and training related to xenophobia, and that services must be related to the specific needs of the victims